Evaluation and optimization of the coagulation-flocculation process using conventional rice starch in potable water treatment - Chua, S.-C. (Institute of Physics Publishing, 2020)
In this study, the application of conventional rice starch as coagulant in potable water treatment has been assessed. Rice starch was found to gelatinize at 83 Â°C for effective flocculation. Besides, respond surface method (RSM) was used to identify the significant factors and to optimize the turbidity reduction in potable water treatment. pH, dosage of starch and settling time were identified as significant factors. To achieve the maximum turbidity reduction (89), the optimum conditions of the factors are with 9.64 mg/L dosage of starch, 20 min of settling time and pH 3. Interestingly, increase of dosage of starch can reduce up to 20 times of settling time which enhance the feasibility of starch to use in the potable water treatment industry. Validation test was conducted to validate the predicted data from designed model. Â© Published under licence by IOP Publishing Ltd.